2022
DOI: 10.1093/cvr/cvac066.008
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis and comparative characterization of rat H9C2, human AC16 and murine HL-1 cardiac cell lines

Abstract: Funding Acknowledgements Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Union's Horizon 2020 research and innovation programme National Research, Development and Innovation Fund of Hungary Background Cardiac cell lines and primary cell cultures are widely used to model various cardiovascular diseases in vitro. Despite the increasing number of publications using these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A recent study in which AC16 cells were exposed to a limited range of PEF treatments showed how human cardiomyocytes in a monolayer culture could be used to determine the relationship between ablation threshold and PEF parameters ( Baena-Montes et al, 2022 ). While the study supports the feasibility of in vitro assessment of PEF cardiac ablation, AC16 expression patterns of mRNA profile and cardiomyocyte markers showed low similarity to primary cells regardless of the differentiation method adopted ( Gulyas-Onodi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 64%
“…A recent study in which AC16 cells were exposed to a limited range of PEF treatments showed how human cardiomyocytes in a monolayer culture could be used to determine the relationship between ablation threshold and PEF parameters ( Baena-Montes et al, 2022 ). While the study supports the feasibility of in vitro assessment of PEF cardiac ablation, AC16 expression patterns of mRNA profile and cardiomyocyte markers showed low similarity to primary cells regardless of the differentiation method adopted ( Gulyas-Onodi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 64%